Proceedings of the 9th International Conference on Social Media and Society 2018
DOI: 10.1145/3217804.3217929
|View full text |Cite
|
Sign up to set email alerts
|

IRA Propaganda on Twitter

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. The results show that the IRA operates a composite of user accounts tailored to perform specific tasks, with the lion's share of their work focusing on US daily news activity and the diffusion of polarized news across different national contexts. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Existent studies analyse the general behaviour in terms of online tactics of extremist organizations, compare differences in online narratives within religious extremist organizations, identify online narratives that justify violent attacks and martyrdom, and changes in those narratives over time (Caiani & Wagemann, 2009; Vergani & Bliuc, 2015). Other studies explore the behaviour of right‐wing extremist organizations regarding their online narratives and their spread via bots (Farkas & Bastos, 2018), as well as intra‐ (Caiani & Wagemann, 2009) and inter‐group dynamics. Some recent studies report the emergence of novel types of extremism (the so‐called ‘hybridized’ extremism) with a post‐organizational leaderless structure that merge various ideologies (e.g., election fraud, vaccine disinformation, conspiracy theories about global elites, and hateful and exclusionary sentiments) (Davey et al, 2021; Jones & Comerford, 2023) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Existent studies analyse the general behaviour in terms of online tactics of extremist organizations, compare differences in online narratives within religious extremist organizations, identify online narratives that justify violent attacks and martyrdom, and changes in those narratives over time (Caiani & Wagemann, 2009; Vergani & Bliuc, 2015). Other studies explore the behaviour of right‐wing extremist organizations regarding their online narratives and their spread via bots (Farkas & Bastos, 2018), as well as intra‐ (Caiani & Wagemann, 2009) and inter‐group dynamics. Some recent studies report the emergence of novel types of extremism (the so‐called ‘hybridized’ extremism) with a post‐organizational leaderless structure that merge various ideologies (e.g., election fraud, vaccine disinformation, conspiracy theories about global elites, and hateful and exclusionary sentiments) (Davey et al, 2021; Jones & Comerford, 2023) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Informed by previous research that identified IRA propaganda targets (Bastos and Farkas, 2019; Farkas and Bastos, 2018), we applied regular expression to profile descriptions and sampled five distinct groups: Muscovites, Black Lives Matter activists, Conservatives, Trump supporters, and Christians. We identified Russian accounts distributing domestic, white propaganda by querying the database for users that self-reported “Москва” as their location ( n = 206).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst much attention has been directed towards Facebook, and the study of the election-related stories most engaged with on that platform, Twitter is often used as the preferred data source, given dedicated data sets (made available by Twitter or academic researchers) of accounts run by the Internet Research Agency (Farkas and Bastos, 2018). There is a series of studies that rely on Twitter's curated sets as well as on the data robustly collected and shared among data researchers, such as by Clemson University and FiveThirtyEight, mentioned above.…”
Section: Junk News Studies: Digital Methods and Data Journalismmentioning
confidence: 99%